Variation of the inflected infinitive in Portuguese - Vanessa Revheim Cunha; Jill McLendon; Allonah Ezro-Christy (Isogloss, 2025)
This study uses corpus methods to examine a controversial topic in Portuguese syntax (Cunha & Cintra 2016): the variation of the inflected infinitive, an uncommon verbal form that marks the infinitive for person and number but not tense. Previous work by grammarians about the use, structure, and distribution of the inflected infinitive is inconsistent. Pires and Rothman (2009) argue that the inflected infinitive has been lost in colloquial Brazilian Portuguese varieties, only being acquired through schooling and/or through the media. Cunha and Cintra (2016) state that there is variation when the subject of the infinitive is an oblique pronoun. This study uses SketchEngine’s ptTenTen20 corpus (Kilgarriff et al. 2014) to investigate theoretical claims from previous literature. The advantage of web-scrapped corpora like the ptTenTen20 lies in large datasets and meta-annotation for variables of interest. Data were queried from SketchEngine, processed using R script, and analyzed with a fixed-effects logistic regression, using variety, genre, and structure as variables. The inflected infinitive was favored in European Portuguese and with clitic pronouns, with significant but contradictory effects seen for register. This study adds directly to the body of literature about the inflected infinitive in Portuguese, using empirical methods to investigate previous theoretical claims.